Study of Culture Condition for Solid State Fermentation of Sewage Treatment Plant Sludge to Compost - Kabbashi, Nassereldeen Ahmed (2002)
With increasing global wastewater production, disposal of sewage sludge is always problematic. Landfilling sewage sludge is a feasible option and is currently practiced in many parts of the world, including Malaysia. Selangor is the fastest developing state in Malaysia with a population of about 4 million, attracting heavy foreign investments in industrial and trade sectors leading to a higher population flux during the last decade. Due to this industrial growth, considerable amounts of sewage sludge are generated and there is a considerable demand for landfilling. Hence, landfilling of sewage sludge is no more attractive and feasible. Composting has become an established process adding value to a large and growing number of organic byproducts. Even so, composting systems and uses for compost are still evolving. Design, operation and control issues remain key factors leading to the success or failure of the process. Environmental issues, product quality and utilization strategies have yet to be fully optimized for many applications to allow usage of the composting process on a sustainable and economic basis. Recent advances in the design, construction and operation of municipal, industrial and agricultural facilities have brought significant improvements to this field. New techniques for monitoring microbial diversity, specific pathogens and beneficial microorganisms have led to a better understanding of the composting process. It is now recognized that composting offers the potential to alleviate numerous environmental problems.